Management and enforcement of economic rights for economic equality in Ghana: Prospects and challenges - Asamoah, Emmanuel Selase; Ayedze, John Baptist (International journal of economic perspectives, 2026)
Laws can play a crucial role in advancing economic rights and minimizing inequality in developing African countries, with Ghana serving as a case study due to its stable democracy and commitment to rule of law and equality. However, to achieve optimum enforcement of laws, there is a need to inculcate the management functions of planning, organizing, leading and controlling various stakeholders and resources for effectiveness. This paper analyses how the management and enforcement of economic rights, seen as essential for human dignity, may narrow significant gaps in economic inequality. The management principles provide operational, structural, and strategic mechanisms that are necessary for translating legal rights such as the right to work, fair wages, and social security into practice. Using normative and doctrinal legal research, the study reviews Ghanaian constitutional provisions, United Nations guidelines, and key Supreme Court and Commission for Human Rights and Administrative Justice (CHRAJ) decisions to establish how rights-based approaches foster equality. Findings highlight the importance of management of government institutions in realizing economic rights, recommending that state agencies rigorously plan to implement legal protections to decrease inequality. The research supports policy development and urges robust enforcement of laws to promote economic fairness.